Was methane responsible for early earth's oxygen boom?. (Research'eu results magazine)
New research has cast new light on the Earth's early atmosphere, which was dominated by thick clouds of methane. These methane clouds forced hydrogen to leave the atmosphere, allowing today's oxygen-rich air to develop.